The Influence of ChatGPT on Social Science Students: Insights Drawn from Undergraduate Students in the United States - Mohaimenul Islam Jowarder (CV. Literasi Indonesia, 2023)
Recently, the artificial intelligence known as ChatGPT has turned into a global sensation, especially among students. This research paper investigates the influence of this AI-powered chatbot, on undergraduate social science students based on insights drawn from semi-structured interviews. The study aims to understand the level of awareness, adoption, perceived usefulness, and impact of ChatGPT on academic performance. 200 undergraduate students were selected and verbatim transcription was used and later thematic analysis was implemented. We implied our custom code to analyze the data based on sample collection from the students. The findings indicate that most of the participants were aware of ChatGPT and had used it for academic work. Perceived usefulness and ease of use were found to be significant factors that influenced the adoption of this technology. Social influence was also found to be a significant factor, with peer recommendations playing a role in shaping students' attitudes toward new technology. ChatGPT had a positive impact on the academic performance of the participants, particularly in assisting them in understanding difficult concepts and providing them with relevant study materials. The study suggests that chatbots can be valuable tools for learning and academic assistance, particularly in disciplines such as social science that require extensive research and analysis. The findings provide useful insights for educators and researchers seeking to integrate chatbots into existing teaching and learning methods to optimize their benefits. More research is needed to assess the future impacts on students and the education sector alike.